Inferindo Fatores Sócio-Afetivos em Ambientes de Ensino-Aprendizagem Colaborativos Assistidos por Computador - Costa Quarto, Cicero (2006)
Nowadays, socio-affective factors, as cooperation, motivation, socio-cognitive affinity, proactivity, interaction and others, have been well explored in collaborative learning environments. The reason for that is because these factors would play an important role in group collaboration, as well as they would act in the construction of the human being relationships in a socio-cultural perspective. According to the vision of some educational researchers, psico-pedagogues and psychologists, in collaborative learning activities, socio-affective individual abilities should be conjugated in order to produce a collective and effective work in the construction of knowledge. Although some pedagogues and other educational researchers point out the importance of considering those factors in collaborative learning activities, few works are appreciating them. This way, the proposal of this work is to define some socio-affective factors to be inferred in collaborative learning systems in order to promote collaboration in these environments. The work will also show the importance of these socio-factors for those virtual environments. It will be also presented mechanisms for the inference of the considered socio-affective factors.